13(x+6)-3=3+-5

Simple and best practice solution for 13(x+6)-3=3+-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(x+6)-3=3+-5 equation:


Simplifying
13(x + 6) + -3 = 3 + -5

Reorder the terms:
13(6 + x) + -3 = 3 + -5
(6 * 13 + x * 13) + -3 = 3 + -5
(78 + 13x) + -3 = 3 + -5

Reorder the terms:
78 + -3 + 13x = 3 + -5

Combine like terms: 78 + -3 = 75
75 + 13x = 3 + -5

Combine like terms: 3 + -5 = -2
75 + 13x = -2

Solving
75 + 13x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-75' to each side of the equation.
75 + -75 + 13x = -2 + -75

Combine like terms: 75 + -75 = 0
0 + 13x = -2 + -75
13x = -2 + -75

Combine like terms: -2 + -75 = -77
13x = -77

Divide each side by '13'.
x = -5.923076923

Simplifying
x = -5.923076923

See similar equations:

| -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 | | .15x=5.25 | | 3(8+2x)(5+2x)=(14.5+2x)(15+2x) | | x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 | | 2(x-3)/5=12 | | e--36=-5 | | x=5+1 | | 5(n+2)+10=20 | | (6x^3-3x^2+4x)-(4x^2+3x+8)= | | 2x/3+20=30 | | 3(x-2)-x=12+5x | | -2/9r=-8 | | 4p-5=20 | | 2/3x-7/12x=5 | | 2y-6=4(y-2) | | -[10z-(21z+7)]=7+(10z+5) | | 3x-14+5x=10-4x | | 10xy-(2y-x)= | | 2m-18m=48 | | A-14a^4=2 | | 3(n+1)=12 | | 1.22y=y+4+1 | | -x^2+x-5=0 | | 9+y=14-2(y+1) |

Equations solver categories